2-Amino-4-ferrocenyl-5-oxo-5,6,7,8-tetrahydro-4H-chromene-3-carbonitrile monohydrate - Carren Nyapola; David O. Juma; Sizwe J. Zamisa; Eric M. Njogu; Bernard Omondi (IUCrData)
In the title hydrate, [Fe(C5H5)(C15H13N2O2)]·H2O, the pendent ferrocenyl substituent is significantly rotated against the chromene backbone, with a torsion angle of 56.8 (2)°. Rotational disorder is observed in one of the Cp rings of the ferrocenyl substituents. The crystal packing is consolidated by a network of O—H...N, O—H...O, N—H...O and N—H...π hydrogen bonds, prominently involving a solvent water molecule. The water molecule functions as both a hydrogen-bond donor and acceptor, bridging adjacent molecules, leading to the formation of a layer with a distinctive hydrogen-bonded motif propagating parallel to the bc plane